Anti-oxidant inhibition of hyaluronan fragment-induced inflammatory gene expression - Powell Jonathan D; Chan-Li Yee; Collins Samuel L; Black Katharine E; Scheibner Kara A; Eberlein Michael; Horton Maureen R (BMC, 2008)
Abstract Background The balance between reactive oxygen species (ROS) and endogenous anti-oxidants is important in maintaining healthy tissues. Excessive ROS states occur in diseases such as ARDS and Idiopathic Pulmonary Fibrosis. Redox imbalance breaks down the extracellular matrix component hyaluronan (HA) into fragments that activate innate immune responses and perpetuate tissue injury. HA fragments, via a TLR and NF-κB pathway, induce inflammatory gene expression in macrophages and epithelial cells. NAC and DMSO are potent anti-oxidants which may help balance excess ROS states. Methods We evaluated the effect of H2O2, NAC and DMSO on HA fragment induced inflammatory gene expression in alveolar macrophages and epithelial cells. Results NAC and DMSO inhibit HA fragment-induced expression of TNF-α and KC protein in alveolar and peritoneal macrophages. NAC and DMSO also show a dose dependent inhibition of IP-10 protein expression, but not IL-8 protein, in alveolar epithelial cells. In addition, H2O2 synergizes with HA fragments to induce inflammatory genes, which are inhibited by NAC. Mechanistically, NAC and DMSO inhibit HA induced gene expression by inhibiting NF-κB activation, but NAC had no influence on HA-fragment-AP-1 mediated gene expression. Conclusion ROS play a central role in a pathophysiologic "vicious cycle" of inflammation: tissue injury generates ROS, which fragment the extracellular matrix HA, which in turn synergize with ROS to activate the innate immune system and further promote ROS, HA fragment generation, inflammation, tissue injury and ultimately fibrosis. The anti-oxidants NAC and DMSO, by inhibiting the HA induced inflammatory gene expression, may help re-balance excessive ROS induced inflammation.